2012
DOI: 10.1042/bj20120750
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyl diphosphate synthase, the target for nitrogen-containing bisphosphonate drugs, is a peroxisomal enzyme in the model system Dictyostelium discoideum

Abstract: NBP (nitrogen-containing bisphosphonate) drugs protect against excessive osteoclast-mediated bone resorption. After binding to bone mineral, they are taken up selectively by the osteoclasts and inhibit the essential enzyme FDPS (farnesyl diphosphate synthase). NBPs inhibit also growth of amoebae of Dictyostelium discoideum in which their target is again FDPS. A fusion protein between FDPS and GFP (green fluorescent protein) was found, in D. discoideum, to localize to peroxisomes and to confer resistance to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The soil-dwelling amoeba Dictyostelium discoideum is known for its remarkable life cycle, which makes it an ideal model organism to study a range of biological problems, such as the mechanisms of action of both first generation [171,172] and nitrogen-containing bisphosphonates [173]. These studies indicate that bisphosphonates are able to cross peroxisomal membranes before they can exert inhibitory action.…”
Section: Scheme (8)mentioning
confidence: 99%
“…The soil-dwelling amoeba Dictyostelium discoideum is known for its remarkable life cycle, which makes it an ideal model organism to study a range of biological problems, such as the mechanisms of action of both first generation [171,172] and nitrogen-containing bisphosphonates [173]. These studies indicate that bisphosphonates are able to cross peroxisomal membranes before they can exert inhibitory action.…”
Section: Scheme (8)mentioning
confidence: 99%
“…In Dictyostelium, two peroxisomal enzymes, the multifunctional enzyme MFE1 (Matsuoka et al, 2003) and citrate synthase CshA (Huang et al, 2004), have been well characterized, which have a C-terminal PTS-1 and an N-terminal PTS-2, respectively. Recently, Nuttall et al (2012) reported that Dictyostelium farnesyl diphosphate synthase possesses a nonapeptide closely related to that of PTS-2 and that it is a peroxisomal enzyme imported through the PTS-2 pathway. It has also been reported that fatty-acyl-CoA synthase B (FcsB) is transported to peroxisomes by mPTS (the targeting signal for peroxisomal membrane proteins) through the Pex19 machinery via the endoplasmic reticulum (ER) (Paschke et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Bisphosphonates (BPs) are a class of drugs that are used to treat resorptive bone diseases like osteoporosis. 7 They mainly inhibit osteoclast action by different ways. They also have effect on other cells like osteoblasts, keratinocytes, fibroblasts and stem cells.…”
Section: Introductionmentioning
confidence: 99%